Development of a TCR-like antibody and chimeric antigen receptor against NY-ESO-1/HLA-A2 for cancer immunotherapy - Xin Liu; Yang Du; Ningyan Zhang; Zhiqiang An; Wei Xiong; Yixiang Xu; Bingnan Yin; Yuqian Huang; Junjun Chu; Changsheng Xing; Chen Qian; Tianhao Duan; et al. (Journal for ImmunoTherapy of Cancer)
Background The current therapeutic antibodies and chimeric antigen receptor (CAR) T cells are capable of recognizing surface antigens, but not of intracellular proteins, thus limiting the target coverage for drug development. To mimic the feature of T-cell receptor (TCR) that recognizes the complex of major histocompatibility class I and peptide on the cell surface derived from the processed intracellular antigen, we used NY-ESO-1, a cancer-testis antigen, to develop a TCR-like fully human IgG1 antibody and its derivative, CAR-T cells, for cancer immunotherapy.Methods Human single-chain variable antibody fragment (scFv) phage library (~10∧11) was screened against HLA-A2/NY-ESO-1 (peptide 157–165) complex to obtain target-specific antibodies. The specificity and affinity of those antibodies were characterized by flow cytometry, ELISA, biolayer interferometry, and confocal imaging. The biological functions of CAR-T cells were evaluated against target tumor cells in vitro. In vivo antitumor activity was investigated in a triple-negative breast cancer (TNBC) model and primary melanoma tumor model in immunocompromised mice.Results Monoclonal antibody 2D2 identified from phage-displayed library specifically bound to NY-ESO-1157-165 in the context of human leukocyte antigen HLA-A*02:01 but not to non-A2 or NY-ESO-1 negative cells. The second-generation CAR-T cells engineered from 2D2 specifically recognized and eliminated A2+/NY-ESO-1+tumor cells in vitro, inhibited tumor growth, and prolonged the overall survival of mice in TNBC and primary melanoma tumor model in vivo.Conclusions This study showed the specificity of the antibody identified from human scFv phage library and demonstrated the potential antitumor activity by TCR-like CAR-T cells both in vitro and in vivo, warranting further preclinical and clinical evaluation of the TCR-like antibody in patients. The generation of TCR-like antibody and its CAR-T cells provides the state-of-the-art platform and proof-of-concept validation to broaden the scope of target antigen recognition and sheds light on the development of novel therapeutics for cancer immunotherapy.